Предмет: Алгебра,
автор: alinakuprina678
помогите решить
заранее спасибо
Приложения:
Ответы
Автор ответа:
0
Ответ:
a) x^2+12x-6^2 - x^2+5^2 = 79
12x-36+25=79
12x=79+36-25
12x=90:12
x= 7,5
b) (4x^2-12x+9) - (7^2-28x+4x^2) = 2
4x^2 - 12x + 9 - 49 + 28x - 4x^2 = 2
16x = 2-9+49:16
x= 2.3
a) x^2+12x-6^2 - x^2+5^2 = 79
12x-36+25=79
12x=79+36-25
12x=90:12
x= 7,5
b) (4x^2-12x+9) - (7^2-28x+4x^2) = 2
4x^2 - 12x + 9 - 49 + 28x - 4x^2 = 2
16x = 2-9+49:16
x= 2.3
Похожие вопросы
Предмет: Русский язык,
автор: StupidLama
Предмет: Русский язык,
автор: 140919990000000
Предмет: Английский язык,
автор: malishh
Предмет: Математика,
автор: egor12343216
Предмет: Литература,
автор: iloveunicornunicorn